Science as a commons: Motivations for continued participation in citizen science projects - Maite Pelacho; Santos Orejudo; Jesús Clemente-Gallardo (PLoS ONE, 2025)
The study of the commons is a growing field of research that is highly relevant to fostering the sustainability of shared resources, including knowledge resources. Citizen science has great potential to constitute science as a knowledge commons, in which continued participation is essential for the long-term viability of inherently collaborative projects and the strengthening of communities. However, different motivations for participation can significantly influence continued engagement, and, consequently, the sustainability of these projects. This research explores, first, participants’ motivations for joining and continuing projects, as well as the reasons for abandoning them. Secondly, we analyse the influence of various motivations on continuity, with a particular focus on highly committed participants—an aspect hitherto scarcely investigated. Specifically, we examine whether these participants’ motivations are primarily associated with general interests (e.g., resource sustainability) alongside personal interests (e.g., capability building). This approach aligns with the key finding of commons theory, which challenges the idea that rational behaviour implies only self-interest. The analyses of 478 responses to the survey designed for this study reveal that participants who sustain CS projects through continued participation are driven by a combination of personal and general interests. These findings reflect cooperative behaviours characteristic of individuals who create or maintain commons. Therefore, we propose that science can be understood as a commons that can be collaboratively and sustainably managed by multiple, decentralized communities. Consequently, fostering cooperation is essential for the effective management of shared resources, particularly in citizen science projects. Enhancing our understanding of cooperation enables the better and more effective implementation of specific recommendations, such as optimizing communication among all those involved in citizen science projects and fostering awareness of common goals and collective achievements. In turn, this reinforces personal benefits, creating a virtuous circle that further strengthens cooperation and its benefits.